2021
DOI: 10.1038/s41598-021-93075-1
|View full text |Cite
|
Sign up to set email alerts
|

Plasma concentrations of granulocyte colony-stimulating factor (G-CSF) in patients with substance use disorders and comorbid major depressive disorder

Abstract: Granulocyte colony–stimulating factor (G-CSF) has raised much interest because of its role in cocaine addiction in preclinical models. We explored the plasma concentrations of G-CSF in patients diagnosed with substance use disorder (SUD) and highly comorbid psychiatric disorders. In particular, we investigated the association between G-CSF concentrations and comorbid major depressive disorder (MDD) in patients with cocaine and alcohol use disorders (CUD and AUD, respectively). Additionally, patients with MDD b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…The dysregulation in G-CSF plasma concentration in the CUD group aligns with a previous study conducted in a cohort of patients diagnosed with substance use disorders and a high prevalence of comorbid depression [26]. A preclinical investigation has reported an association between G-CSF expression and the seeking and consumption of cocaine [25], which could explain the reduced concentrations observed during abstinence from cocaine in the CUD group.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The dysregulation in G-CSF plasma concentration in the CUD group aligns with a previous study conducted in a cohort of patients diagnosed with substance use disorders and a high prevalence of comorbid depression [26]. A preclinical investigation has reported an association between G-CSF expression and the seeking and consumption of cocaine [25], which could explain the reduced concentrations observed during abstinence from cocaine in the CUD group.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, our research group recently undertook a study involving patients with polysubstance use disorders, specifically alcohol. This research unveiled an association between differences in plasma concentrations of G-CSF and comorbid major depression, suggesting a potential contribution to the stratification of these patients seeking treatment [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Variables related to abstinence, severity of SUD (calculated with the addition of criteria for SUD based on the current DSM-5), mental and medical comorbidity, psychotropic medication use were collected for this study. Control individuals were evaluated with the Spanish version of the Composite International Diagnostic Interview (CIDI) for the identification of mental disorders [32] and the PRISM module 1 for sociodemographic and physiological variables [23,33].…”
Section: Clinical Evaluationsmentioning
confidence: 99%
“…found an inverse relationship between serum G-CSF levels and age in substance use disorder (SUD) compared to HCs [62]. However, Dahl et al revealed that plasma G-CSF levels became normalized during the recovery phase of depressive episodes in MDD patients [63].…”
Section: Plos Onementioning
confidence: 99%